Study on the morphology and digestive system development in early life stages of kelah , Tor tambroides (bleeker, 1854) - Endryeni M. (2011)
A study on external morphology and digestive system development of Tor tambroides were conducted at Institute of Tropical Aquaculture of Universiti Malaysia Terengganu from newly hatched larvae until 45 day after hatching (DAH) by morphological measurement and histological technique. This study is to provide information for the best rearing management based on the development and behaviour of this fish. Information on digestive system development can improve the feeding strategy of this species.